Antidepressant treatment effects and country income: meta‐regression analysis of individual participant data from duloxetine trials. (5th July 2021) - Klein, Thomas; Weinmann, Stefan; Becker, Thomas; Koesters, Markus
Abstract: Objective: In recent decades, significant numbers of pharmaceutical trials have gradually been relocated to low‐ and middle‐income countries. However, there is little evidence regarding the transferability of trial outcomes across countries. Analysing duloxetine randomised controlled trials (RCTs) conducted in different countries, we investigated whether per capita gross national income (GNI) and healthcare expenditure (HE) are associated with pre‐post mean changes of depression severity and differences in duloxetine‐placebo effect sizes. Method: Meta‐analyses included RCTs investigating duloxetine efficacy in patients with depression. Individual participant data (IPD) from multi‐centre duloxetine trials were provided by the manufacturer. Data extracted from published reports also entered analyses in case of trials conducted in only one country. A meta‐regression approach was applied to analyse associations of GNI and HE with standardised pre‐post mean change using raw score standardisation (SMCR) and comparative effect size, that is, the mean differences (MD) in pre‐post effect size between duloxetine and placebo treatment. Results: 23 trials with 8417 randomised participants entered analyses. Regression coefficients indicated a negative linear relationship of SMCR with GNI (z‐standardised β  = −3.61, R 2  = 14.8%, p < 0.001) and HE ( β  = −4.72, R 2  = 24.8%, p < 0.001) for participants treated with duloxetine. Similar associations were found for placebo treatment (GNI: β  = −3.52, R 2  = 23.8%, p < 0.001; β  = −3.34, R 2  = 21.0% p < 0.001). Neither GNI nor HE was associated with the MD between duloxetine and placebo pre‐post differences. Conclusions: Findings challenge the idea of the universal transferability of antidepressant trial outcomes across countries. Understanding the results of antidepressant RCTs demands more sophisticated clarification of context factors involved in determining effectiveness of antidepressant medication and should be discussed with a view to socio‐economic context in their countries of origin.